Revisiting the Concept of Mar'ah in the Qur'an: A Thematic AnalysiThe Concept of Mar’ah in the Qur’an and Its Relevance to the Character Education of Muslim Womens of Women's Spiritual, Social, and Moral Dimensions - Mardan Mardan; Muhammad Asmariadi Arsyad; Muhsin Muhsin (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study examines the concept of Mar'ah (women) in the Qur'an through the thematic interpretation approach. The research was motivated by the continuing debate regarding the position and role of women in Islam, which is often understood through partial interpretations of individual Qur'anic verses without considering their thematic unity. Employing a qualitative library research design, this study systematically collected and analyzed Qur'anic verses related to women by examining their linguistic meanings, semantic structures, contexts of revelation (asbab al-nuzul), Makkiyah-Madaniyah classifications, interrelationships among verses (munasabah), classical and contemporary Qur'anic exegesis, and relevant prophetic traditions. The findings reveal that the Qur'an employs various terms to describe women, including mar'ah, an-nisa', untha, zauj, umm, and banat, each representing distinct biological, relational, social, and spiritual dimensions. The study further demonstrates that the Qur'anic concept of women is constructed gradually, beginning with the establishment of theological and moral principles during the Makkan period and continuing with the regulation of social and family life during the Madinan period. Rather than portraying women as subordinate to men, the Qur'an presents women as independent moral agents possessing equal spiritual responsibility before Allah while simultaneously recognizing their complementary roles within family and society. The novelty of this research lies in its integrative thematic interpretation that combines linguistic, semantic, exegetical, and prophetic analyses to formulate a comprehensive conceptual framework of women in the Qur'an. The findings contribute to the development of Qur'anic studies, Islamic gender discourse, Islamic education, and contemporary Islamic thought concerning women's dignity and social participation.